Subjunctive and Interpassive “Knowing” in the Surveillance Society - Sun-ha Hong (Media and Communication, 2015)
The Snowden affair marked not a switch from ignorance to informed enlightenment, but a problematisation of knowing as a condition. What does it mean to know of a surveillance apparatus that recedes from your sensory experience at every turn? How do we mobilise that knowledge for opinion and action when its benefits and harms are only articulable in terms of future-forwarded “as if”s? If the extent, legality and efficacy of surveillance is allegedly proven in secrecy, what kind of knowledge can we be said to “possess”? This essay characterises such knowing as “world-building”. We cobble together facts, claims, hypotheticals into a set of often speculative and deferred foundations for thought, opinion, feeling, action. Surveillance technology’s recession from everyday life accentuates this process. Based on close analysis of the public mediated discourse on the Snowden affair, I offer two common patterns of such world-building or knowing. They are (1) subjunctivity, the conceit of “I cannot know, but I must act as if it is true”; (2) interpassivity, which says “I don’t believe it/I am not affected, but someone else is (in my stead)”.